2019
DOI: 10.18203/2349-3933.ijam20194135
|View full text |Cite
|
Sign up to set email alerts
|

Study of gastrointestinal manifestations in Dengue fever

Abstract: Background: Dengue is an arthropod borne viral haemorrhagic fever. In India between 2015-2017, 790 deaths have been recorded according to NVBDCP data. Gastrointestinal manifestations are among the most common manifestations in dengue fever, and are most often missed due to lack of awareness. This study aims to find the spectrum of Gastrointestinal manifestations and correlation of GI manifestations with severity of Dengue.Methods: A cross-sectional observational study was conducted on 100 consecutive cases of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Clinical features of hepatic involvement found in various series were abdominal pain (18% to 63%), nausea with or without vomiting (49% to 58%) and anorexia (31% to 44%) [16,17,18] . The frequency of hepatomegaly in adult patients ranged from 4% to 52%.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Clinical features of hepatic involvement found in various series were abdominal pain (18% to 63%), nausea with or without vomiting (49% to 58%) and anorexia (31% to 44%) [16,17,18] . The frequency of hepatomegaly in adult patients ranged from 4% to 52%.…”
Section: Discussionmentioning
confidence: 93%
“…16.3% cases had serum bilirubin>5 mg/dl in the study by Saha AK et al [19] Literature review revealed that raised transaminase levels was the commonest biochemical abnormality. Increased AST levels was seen in 63% -97% of patients, while raised ALT levels in 45 -96% of patients [5,17,18,22,23] . Elevation in AST was more than ALT, more during the first week of infection, with a tendency to decrease to normal levels within three weeks [5,23] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For infecting cells, the major rate limiting step is the viral attachment to the receptors present on surface of host cell. An eventual outcome of hepatocyte infection by DENV is cellular apoptosis, a phenomenon demonstrated both in vivo and in vitro 10 . This study was aimed to describe the gastro intestinal manifestations of dengue infected children during 2019 dengue outbreak in Dhaka city.…”
mentioning
confidence: 99%